Analysis Forms of Political Communication in Campaign Strategies to Increase Voter Participation in the 2024 Sumut Regional Elections - Jannah, Nurul Ainun; Sampurna, Ahmad; Hasibuan, Manita Rahma; Ardianti, Indah; Barry, Ahlan Adib AL (LPPPIPublishing, 2024)
This research examines the forms of political communication in the campaign strategy to increase voter participation in the 2024 North Sumatra regional elections. This research aims to identify and analyze the forms of political communication used in the 2024 North Sumatra regional election campaign strategy and evaluate their effectiveness in increasing voter participation. This research uses a qualitative approach using the case study method. Data collection techniques in this research are observation, interviews and documentation. The research results reveal that various forms of political communication have an important role in increasing voter participation in the 2024 North Sumatra regional elections. Interpersonal communication through door-to-door campaigns and community meetings increases voter confidence. Mass media such as television, radio and newspapers help shape public opinion. Social media is effective in reaching young and urban voters. Political debates and speeches provide an opportunity for candidates to present their work programs. Door-to-door campaigns remain effective in rural areas. This combination of various forms of political communication has proven effective in increasing voter participation.